PEMANFAATAN BENANG WOL MENJADI GELANG YANG BERNILAI JUAL UNTUK ANAK-ANAK DESA TANJUNG MAKMUR, KECAMATAN SINAR PENINJAUAN, KABUPATEN OGAN KOMERING ULU - Anis Feblin; Meika Debiansyah; Syahrinda Abyadi; Ana Riski Setiani; Melin Oktarini (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Wool thread is a type of material that can be used to make handicrafts. Wool thread has unique characteristics and is different from other threads such as; absorbs surrounding fluids, is not affected by weather, elastic, resistant to dust and dirt, not easily dirty, easy to clean (Astuti, P, 2018). The method used is through socialization, exposure and practicum using simple braiding techniques. The results of this activity show that children do not know how to use wool thread to make a bracelet using the braiding technique. By carrying out this activity, it is hoped that children in Tanjung Makmur Village will be able to use wool thread to make bracelets that have sales value